New data on distribution and molecular genetics of Lignyoptera fumidaria (Hübner, [1825]) (Lepidoptera: Geometridae) - S. A. Knyazev; A. U. Gabdullina; I. A. Makhov (SHILAP, 2021)
The rare and little known late-autumn species Lignyoptera fumidaria (Hübner, [1825]) is reported from Katon-Karagai National Park (Eastern Kazakhstan) for the first time. The present record is the second in Eastern Kazakhstan. The general species’ distribution provided. Species’ habitats in Katon-Karagai district of Eastern Kazakhstan are illustrated. Molecular data on the specimens from Kazakhstan studied for the first time